Reason, Law, and the Common Good: Foundations of the Philosophy of Law in Saint Thomas Aquinas and Its Relevance in Contemporary Legal Thought - Fattah Jedlres, Javier Ignacio (Universidad Hemisferios, 2026)
This article analyzes the foundations of the philosophy of law in the thought of Saint Thomas Aquinas, with the aim of presenting its central concepts and evaluating their relevance in light of the challenges of contemporary legal thought. Through a hermeneutic and analytical methodology, the four essential elements of the Thomistic definition of law are examined: rationality, orientation toward the common good, legitimate authority, and finally promulgation, as well as the normative hierarchy that articulates eternal law, natural law, and human law. The notion of law as ipsa res iusta is also analyzed, along with the distinction between natural law, the law of nations, and positive law, and the role of the common good as a criterion of legal legitimacy. The article concludes that Thomism does not constitute an anachronistic philosophical system, but rather a tradition of thought capable of offering responses to the problems posed by legal positivism, normative relativism, and the tensions between power and justice that characterize contemporary legal reflection.